Segregation and mistrust : diversity, isolation, and social cohesion - Uslaner, Eric M. (Cambridge : Cambridge University Press, 2012)
'Eric M. Uslaner examines the theoretical and measurement differences between segregation and diversity and summarizes results on how integrated neighborhoods with diverse social networks increase trust in the United States, Canada, the United Kingdom, Sweden, and Australia'--
Includes bibliographical references (pages 227-254) and index.
Keywords: Race relations; Trust; Segregation; Multiculturalism; Cultural pluralism